2020
DOI: 10.3390/ma13245731
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Asphalt Mixtures Containing Metallic Fibers from Recycled Tires to Promote Crack-Healing

Abstract: This paper reports part of an international research project with the long-term aim of developing more sustainable asphalt mixture with crack-healing properties by the addition of recycled metallic waste from industrial sources. Specifically, this article presents an evaluation of the physical, thermophysical, and mechanical properties of asphalt mixtures with metallic fiber obtained from recycled tires for crack-healing purposes. Detailed results on the crack-healing of asphalt mixtures will be reported in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…However, the citations for document of González and Norambuena-Contrera were 56 and 45, respectively. González et al [ 188 ] assessed the performance of hot mix asphalt incorporating amended bitumen with different proportions of metallic fibers of 1.5, 2.5, and 3.5% by bitumen volume. The findings of the study demonstrated that the higher the dosage of fiber, the higher the air void content, clustering, and electrical conductivity.…”
Section: Results and Analysismentioning
confidence: 99%
“…However, the citations for document of González and Norambuena-Contrera were 56 and 45, respectively. González et al [ 188 ] assessed the performance of hot mix asphalt incorporating amended bitumen with different proportions of metallic fibers of 1.5, 2.5, and 3.5% by bitumen volume. The findings of the study demonstrated that the higher the dosage of fiber, the higher the air void content, clustering, and electrical conductivity.…”
Section: Results and Analysismentioning
confidence: 99%
“…The found results are in accord with previous research. The research of González et al (2020) found that when the steel fibers increase, the electrical resistivity increases [28].…”
Section: Steel Fibers Effectmentioning
confidence: 99%
“…Adding fibers improve rut resistance, activate multifunctional applications [21][22][23][24][25][26] and increase crack resistance by fatigue and crack resistance by bending [5,27]. Many previous studies on the electrical conductivity of conducting asphalt concrete showed that conductivity is proportional to the fiber amount added [5,28]. Graphite is one of the most common carbon additives with the most stable crystalline structure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated in numerous studies on the electrical conductivity of conductive bituminous mixes that the conductivity is inversely related to the amount of added fibers [5,28].…”
Section: Introductionmentioning
confidence: 99%